A NOTE ON THE ABNORMAL SPECIMEN OF THRYSSA PURAVA (HAMILTON-BUCHANAN) WITH BLACK PECTORAL FINS KRISHNA ESTUARY - RAO, T.A.; SHARMA, S.V.; RAJU, P.B. JAYA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
Surprising occurance of Thryssa purava with black pectoral fins from Krishna estuary are reported in this communication.